Phonon-Induced Far Infrared Absorption in Superconductors - Farnworth, Brian (My University, 1976)
Phonon induced absorption spectra are presented for a variety of superconductors and compared to phonon densities of states derived from tunneling and neutron scattering experiments. Good signal to noise ratios permit differentiation of the spectra and thereby a direct presentation of the phonon spectrum. A simple weak coupling theory is used to interpret the results. For lead the simple theory is sufficiently accurate to permit inversion of the experimental spectrum to give a phonon density of states which contains fine structure that is in good agreement with neutron, but not tunneling, results. Evidence is found of phonon lifetime effects associated with the superconducting transition. A comparison is made with the full strong coupling theory, but only for the undifferentiated data, showing good agreement. In other materials phonon induced structure is weaker and in poorer agreement with the simple theory.
Keywords: Physics; Physics